Pelatihan Administrasi Data Pada Pengurus Unit Kegiatan Mahasiswa (UKM) Universitas Amikom Purwokerto - Setyaningsih, Gustin; Inayatun, Ulfa; Cahyani, Sinta Nur; Setiawan, Ito (Universitas Pahlawan Tuanku Tambusai, 2023)
One element in student activities is secretarial work or popularly known as the duties of a secretary. This field is very synonymous with administrative matters. In practice, data administration by the management of the Student Activity Unit (UKM) at Amikom Purwokerto University still makes many mistakes, such as when making incomplete proposals, final reports that do not comply with existing guidelines. . This resulted in a long time because they had to submit 2 times, make data corrections so that it hindered the work of the UKM administrators themselves. The aim of UKM data administration training is to help UKM administrators to be more orderly in administration and in accordance with existing guidelines. The methods used in socialization and training are the preparation stage, implementation stage and evaluation stage. The result of the research is that the training participants' knowledge of the basic administration of UKM increases before the training is carried out, the errors in making proposals and other procedures are reduced.